MUSLIM WOMEN AS DRIVERS OF GLOBAL ECONOMIC DEVELOPMENT: OPPORTUNITIES, CHALLENGES, AND CONTRIBUTIONS - Diva Wamanda; Zainal Abidin; Khairani Hayat Situmorang (CV. Barokah Publsiher, 2026)
Muslim women have increasingly emerged as significant contributors to global economic development through their active participation in entrepreneurship, the labor market, education, Islamic finance, and digital innovation. Despite this progress, many continue to face structural, socio-cultural, and institutional barriers that limit their economic potential. This study aims to explore the opportunities, challenges, and contributions of Muslim women to global economic development from the perspective of Islamic economic principles and contemporary literature. Employing a qualitative research design based on library research, the study analyzes scholarly articles, books, international reports, and policy documents published between 2019 and 2025. The collected data were examined using thematic content analysis to identify recurring patterns and emerging themes. The findings reveal that Muslim women contribute significantly to economic growth by increasing household income, fostering entrepreneurship, supporting small and medium-sized enterprises (SMEs), promoting financial inclusion through Islamic finance, and participating in the digital economy. Furthermore, Islamic teachings encourage women's economic participation while emphasizing justice, dignity, responsibility, and ethical business practices. However, persistent challenges including gender inequality, limited access to education and finance, digital disparities, and restrictive socio-cultural norms continue to hinder their full participation. The study concludes that empowering Muslim women through inclusive education, financial access, supportive public policies, digital literacy, and gender-responsive Islamic economic frameworks can strengthen sustainable and inclusive global economic development. These findings provide valuable insights for policymakers, educators, researchers, and development institutions seeking to enhance women's economic empowerment within an Islamic context.